The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2002
DOI: 10.1182/blood.v99.5.1840
|View full text |Cite
|
Sign up to set email alerts
|

A cure for murine sickle cell disease through stable mixed chimerism and tolerance induction after nonmyeloablative conditioning and major histocompatibility complex–mismatched bone marrow transplantation

Abstract: The morbidity and mortality associated with sickle cell disease (SCD) is caused by hemolytic anemia, vaso-occlusion, and progressive multiorgan damage. Bone marrow transplantation (BMT) is currently the only curative therapy; however, toxic myeloablative preconditioning and barriers to allotransplantation limit this therapy to children with major SCD complications and HLA-matched donors. In trials of myeloablative BMT designed to yield total marrow replacement with donor stem cells, a subset of patients develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 38 publications
3
65
0
Order By: Relevance
“…While hemopoietic chimerism has the potential to treat or cure life-threatening conditions (30) and to facilitate tolerance induction to transplants, it also has the potential to adversely affect the ability of a recipient to generate effective immune responses, particularly against intracellular pathogens. It is critical that we understand the degree to which chimerism-based tolerance induction regimens create immunologic blind spots and impair the ability of a recipient to effectively control intracellular pathogens, particularly those that cause persistent or latent infections.…”
Section: Discussionmentioning
confidence: 99%
“…While hemopoietic chimerism has the potential to treat or cure life-threatening conditions (30) and to facilitate tolerance induction to transplants, it also has the potential to adversely affect the ability of a recipient to generate effective immune responses, particularly against intracellular pathogens. It is critical that we understand the degree to which chimerism-based tolerance induction regimens create immunologic blind spots and impair the ability of a recipient to effectively control intracellular pathogens, particularly those that cause persistent or latent infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, this enthusiasm has been short-lasting owing to poor outcome with conventional allografting. 6 Recent developments in reduced-intensity conditioning (RIC) have rendered allogeneic haematopoietic stem cell transplantation (allo-HSCT) feasible in a wider group of patients who could potentially benefit from such a procedure, but who were considered ineligible for conventional conditioning owing to increased age or comorbidities. [7][8][9][10] Various RIC regimens have been employed with differing complications.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Several investigators have shown the potential of non-myeloablative or reduced intensity (RI) conditioning followed by AlloSCT to reduce regimen-related morbidity, regimen-related mortality (RRM) and potentially future late effects in patients with both malignant and nonmalignant disorders. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] A recent review by our group has summarized the results to date following RI conditioning for allogeneic stem cell transplantation (RI-AlloSCT). 35 Recently, successful engraftment has been demonstrated after reduced intensity UCBT (RI-UCBT) in adult recipients.…”
Section: Introductionmentioning
confidence: 99%